Sandwich-structured ion exchange membrane/cotton fabric based flexible high-efficient and constant electricity generator. (18th November 2022) - Wang, Yamei; Zhang, Liwen; Xie, Bingtao; Zhao, Zehui; Zhou, Xinzhao; Yang, Changjun; Chen, Huawei
Abstract: Harvesting energy based on hydrovoltaic effect as a cost-efficient and eco-friendly technology has attracted increasing attention worldwide with the intensification of global energy crisis and the development of wearable electronics. However, the existing hydrovoltaic power generators are characteristic of low electrical output in ionic solutions and high material rigidity, which hinder their application scenarios. Herein, a membrane/fabric hydrovoltaic power generator (MFHPG) with a sandwich structure is proposed, which is made up of ion exchange membrane (IEM) and cotton fabric, distinguished by high-efficient and constant energy generating from salt solution through solar evaporation. Benefiting from the directional flowing of salt solution driven by the capillary of cotton fabric fibres and water evaporation, the IEM selectively transports ions in the salt solution to generate power with much enhanced performance, where a superior short-circuit current ( I sc ) of ∼54.5 μA and an open-circuit voltage ( V oc ) of ∼0.23 V can be obtained with a size of 20 × 10 cm 2 . Experimental results illustrate that surface size, different solution concentrations/types and temperature all have influences on energy output performance. The underlying mechanism has also been established based on elemental composition analysis, Fourier transform infrared (FTIR) spectroscopy and fluid flow observation. Notably, the power output can be readily promoted by series/parallel connections of MFHPGs to operate commercial electronics. This work could open up new materials and expand broader application scenarios in the field of hydrovoltaic power generation. Graphical abstract: Image 1 Highlights: A sandwich generator was firstly fabricated by ion exchange membrane combined with cotton fabric to harvest efficient and constant energy from salt solution through solar evaporation. The generator exhibits high flexibility and achieves superior short-circuit current of ∼54.5 μA with a size of 20 × 10 cm 2 . The generator can be easily integrated to power micro electronic devices.